The Refrigerants and the contributions of scientists Rowland and Molina (Publicaciones en Ciencias y Tecnología, 2021)
The present paper consists of a documentary type investigation, focused on the historical development of refrigerants, emphasizing commercial freons made from chlorine-fluorine-carbons (CFCs), which generated the first questioning as ozone exhausting , based on the valuable contribution to humanity of  Mario Molina and Sherwood Rowland, awarded the 1995 Nobel Prize in Chemistry, by demonstrating to the world the damage caused to the ozone layer and being pioneers in the solution, starting with the Montreal protocol. Additionally, it describes the fate of the refrigerants, exposing current studies. Thanks to the work done by Molina and Rowland in combining the relationship between science, industry and diplomatic activity, it is possible to see results that translate into transcendental benefits to the planet. The use of refrigeration will continue, but research should continue to increase knowledge in techniques that do not deteriorate the environment, thus considering ozone for life, for preservation and future life.
Keywords: ozone layer; freons; refrigerants; Mario Molina; atmosphere; Sherwood Rowland